Fiscal and Monetary Policy During Downturns : Evidence From the G7 - Stehn, Sven Jari.; Leigh, Daniel (Washington, D.C. : International Monetary Fund, 2009)
This paper analyzes how fiscal and monetary policy typically respond during downturns in G7 countries. It evaluates whether discretionary fiscal responses to downturns are timely and temporary, and compares the response of fiscal policy to that of monetary policy. The results suggest that while responding more weakly and less quickly than monetary policy, discretionary fiscal policy is more timely than conventional wisdom would suggest, particularly in 'Anglo-Saxon' countries, but the response differs substantially across fiscal instruments. Both fiscal and monetary policy are found to be subject to an easing bias, with more easing during downturns than tightening during upturns; and liable to easing in response to erroneously perceived downturns, many of which are subsequently revised to expansions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet